Menuju Haji Inklusif: Urgensi Prosedur Penanganan Jemaah Demensia di Kementerian Agama RI - Wasal Sani (JURNAL ILMIAH GEMA PERENCANA, 2025)
The government, through the Ministry of Religious Affairs, continues to strive to improve the quality of Hajj services for all Indonesian pilgrims. However, as the number of elderly pilgrims increases, significant issues have emerged regarding services for pilgrims with dementia. This study analyzed three main issues: the inability of pilgrims with dementia to perform their pilgrimage optimally, the difficulties faced by officials and companions in providing assistance, and systemic weaknesses in Hajj governance. The analysis used the USG (Urgency, Seriousness, Growth) theory to prioritize the issues, indicating that both the direct impact on pilgrims and the systemic weaknesses have very high levels of urgency and seriousness. The main root causes were identified as the lack of clear regulations and policies, the lack of comprehensive data and research, and limited training and resources for officials. To address these issues, three alternative policies were developed: a dedicated integrated policy, capacity building for officials, and partnerships with external parties. Policy evaluation using Dunn scoring analysis indicated that the integrated approach was the most effective, although difficult to implement. Therefore, the proposed policy recommendation is to enact regulations mandating the implementation of a combined strategy. This regulation adopts an integrated policy as a long-term vision, while immediately implementing comprehensive training for officers and establishing strategic partnerships as tactical solutions. The goal is to create an inclusive, fair, and equitable Hajj service, ensuring that every pilgrim can perform their pilgrimage safely and with dignity, in accordance with the principles of Maqasid al-Shari'ah.